Direct electrochemical grafting of crystalline PAEK macromolecule on carbon fiber to enhance the interfacial properties of PEEK/CF composites - Wang, Shengdao; Zhang, Shuwen; Yang, Yanchao; Dong, Zhongxin; Wang, Guibin (Composites science and technology, 2022)
Electrochemical grafting of diazonium salts have been applied to improve interfacial properties of carbon fiber and matrix resin. However, these graft modifications are still limited to general-purpose carbon fiber reinforced resin matrix composites such as epoxy. In this research, the direct grafting of Poly (aryl ether ketone) (PAEK) macromolecule on carbon fiber was achieved with mild condition. Firstly, aniline was introduced into Poly (ether ether ketone) (PEEK) as pendent group to improve solubility and amino terminated group was introduced as precursor of diazonium salt. Then the graft was conduct through diazonium salt reduction. After modification, the aniline side group could be hydrolyzed off to recover crystallinity. To further analyze the graft, single molecular-force spectroscopy was introduced to investigate the surface of carbon fiber. Impressively, the extension curve suggested the PAEK macromolecule had been attached to surface through strong interaction. Combined this with XPS data, it was believed that the graft was a success. As a result, the grafted polymer along with the polymer that physically absorbed on carbon fiber in electrolyte can cooperate to strengthen the interface. The interfacial shear strength of the grafted carbon fiber and PEEK increased from 42.27 MPa to 97.33 MPa by 130.26%. The improvement mainly originated from the covalent bonding that connected the carbon fiber and the graft coating layer as well as the great compatibility between the graft coating layer and the matrix resin. These results also demonstrated the possibility to graft high performance polymers on carbon fiber through one-step modifications. [Display omitted] •The PAEK macromolecules were directly grafted on CF by electrochemical grafting for the first time.•The polymer at the interface was characterized by single-molecule force spectroscopy,suggesting the success of grafting.•The amino terminated PAEK and PAEK macromolecular diazonium salt were synthesized.•The grafted PAEK polymer along with coated PAEK could significantly improve the IFSS of carbon fiber and PEEK resin.